Effectiveness, Growth Rate and Contribution of Local Tax Revenue, Local Retribution, Results of Management of Separated Regional Wealth and Other Legitimate Local Revenue to Kediri District Local Revenue - Siswati, Susi; Kaloeti, Ade Kristianus (KINERJA, 2024)
The purpose of this study was to determine the effectiveness, growth rate, and contribution of local taxes, local levies, the results of the management of separated local assets, other legitimate RLI to local revenue. The sample comprises the five-year budgetary framework of the Regional Revenue and Expenditure Budget (APBD) for Kediri Regency during the period from 2018 to 2022. The current phenomenon observed in the budget reports and realizations established within the framework of the Regional Revenue and Expenditure Budget (APBD) of Kediri Regency pertains to local taxes, regional levies, the management of separated regional wealth, and other legitimate sources of local revenue. Specifically, an analysis of the budget and realization from 2018 to 2022 reveals discrepancies in revenue generation year over year, alongside an examination of the growth rates and their contributions to overall revenue. These discrepancies serve as a basis for evaluating the effectiveness of the budget as set forth in the APBD of Kediri Regency. Consequently, it is imperative to conduct research focused on the effectiveness, growth rates, and contributions of these revenues to local income. A detailed examination of the budget and realization data from 2018 to 2022 indicates notable variations in revenue collection from year to year, as well as an analysis of the growth trends and their respective contributions to total revenue. These variations will inform the assessment of whether the budget, as established by the APBD of Kediri Regency, is effective or not. Therefore, it is essential to undertake research that investigates the effectiveness, growth rates, and contributions of these revenues to local income. Data analysis techniques and mathematical methods used are effectiveness ratio, growth rate ratio, and contribution ratio. Data collected from the APBD posture in Kediri district for the period 2018 - 2022. The results of the analysis of the effectiveness ratio for the period 2018 - 2022 for local taxes are very effective because all exceed 100%, the highest local retribution in 2018 is 133.22% and the lowest in 2020 is 90.31%. The results of the management of separated regional assets, the effectiveness ratio is in the highly effective category because all exceed 100%, while the highest other legal RLI in 2022 is 173.05% and the lowest in 2018 is 66.22%. The results of the growth rate analysis for local taxes, local levies, and the results of the management of separated assets for the period 2018 - 2022 are all included in the unsuccessful category because all are less than 30%. As for other legitimate RLI, some are unsuccessful but some are less successful in 2019 and 2022 because the percentage is 30%-55%. The highest contribution ratio for local taxes in 2018 of 55.62% is in the very good category because it exceeds 50%, the lowest in 2022 of 37.74% is in the medium category between 30.10% - 40%. For local retribution and the results of managing separated assets are all in the very poor category because they are below 10%. Other legitimate RLI in 2022 amounted to 56.58 very good category, and the lowest in 2018 amounted to 35.73% including the moderate category.